Tolerance of the fetus by the maternal immune system: role of inflammatory mediators at the feto-maternal interface - Verbeke Philippe; Caucheteux Stéphane M; Kanellopoulos-Langevin Colette; Ojcius David M (BMC, 2003)
Abstract The adaptive immune system of placental mammals has evolved to tolerate the fetus. Rejection of the fetus by adaptive immune responses is therefore a rare event, with abortion being caused more frequently by inflammation in the placenta. This review will cover recent aspects of immune privilege and the innate immune system at the feto-maternal interface, citing examples of the role played by microbial infections in fetal demise.